2014
DOI: 10.1159/000356450
|View full text |Cite
|
Sign up to set email alerts
|

Bioimpedance in 7-Year-Old Children: Validation by Dual X-Ray Absorptiometry - Part 1: Assessment of Whole Body Composition

Abstract: Aim: To validate the bioimpedance analyzer (BIA) Tanita BC-418 for its clinical and epidemiological use in children compared to dual-energy X-ray absorptiometry (DXA). Methods: A cross-sectional validation study was performed in 7-year-old children using anthropometry, BIA and DXA. Whole body fat and lean masses were assessed through BIA (BIAoutputs) and DXA. Fat mass index (FMI) was calculated. Predictive equations were derived from raw impedance and anthropometric measures; results obtained from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 20 publications
1
25
0
4
Order By: Relevance
“…Finally, using gold-standard measures of body composition such as dual-energy X-ray absorptiometry (DEXA) would have been preferable, but is too costly to be applied in such large samples as the present. Notably though, bioimpedance analyses of children’s body composition is found to be valid as tested against DEXA [44] and Tanita scales are considered accurate and efficient means of assessing body composition in epidemiological studies of elementary school children [4446]. …”
Section: Discussionmentioning
confidence: 99%
“…Finally, using gold-standard measures of body composition such as dual-energy X-ray absorptiometry (DEXA) would have been preferable, but is too costly to be applied in such large samples as the present. Notably though, bioimpedance analyses of children’s body composition is found to be valid as tested against DEXA [44] and Tanita scales are considered accurate and efficient means of assessing body composition in epidemiological studies of elementary school children [4446]. …”
Section: Discussionmentioning
confidence: 99%
“…Body Fat Percentage: A bioelectric impedance scale (Tanita BC-568 Inner-Scan Segmental Body Composition Monitor, Tanita, Arligton, IL, USA) was used to estimate body fat percentage [20]. To complete this assessment, each child stood on the bioelectrical impendence platform with a grip in each hand.…”
Section: Methodsmentioning
confidence: 99%
“…To complete this assessment, each child stood on the bioelectrical impendence platform with a grip in each hand. From this position, a small electrical current was passed through the child’s body and resistance to this electrical current was measured, from which water percentage was estimated [20]. From this estimation, body fat percentage can be estimated.…”
Section: Methodsmentioning
confidence: 99%
“…The number of participants ranged from n ¼ 16 [34] to n ¼ 1125 [44], who were mainly Caucasian ( Table 2). Regarding the participants' age, 10 studies proposed an equation for subjects aged 65 years and older [35,41,45e48,51e53], 9 for adults (age range 24e53 years) [16,31,36e39,42,50,54], 4 for children [32,33,43,49] and 2 did not report the age of the study population [34,40]. Most studies included healthy participants, except for some specific populations such as obese children [32,33], adults with chronic kidney diseases [41,42], healthy adults but at risk of osteopenia [38], and older subjects presenting sarcopenia or frailty [51,53].…”
Section: Studies Characteristicsmentioning
confidence: 99%
“…Regarding BIA devices used, it is observed that: 1) Different brands of BIA have been used throughout the studies: among them, 5 studies reported using the Inbody device [16,39,42,44,46], 8 used the RJL systems [35,37,38,43,47,49,52,53], 4 studies reported using the Tanita system [32,33,45,50], 3 used the Xitron devices [40,41,51] and the 5 last ones used other devices [31,34,36,48,54]. However, among the same brand of BIA devices a large diversity is also observed regarding the version of the devices used.…”
Section: Muscle Mass Assessmentmentioning
confidence: 99%